Design guidelines for residential envelope openings in the equatorial tropics : Studies in suburban housing in the cauca valley of Colombia (2012)
The envelope openings of houses have a strong implication in the indoor environmental quality and energy consumption, however, there are no precise regulations for its design, especially in particular climate zones such as the tropics, where there are no recommendations or laws for residential architecture. This has not only deteriorated the environmental quality, but also increased energy consumption in new buildings. Therefore comprehensive reviews of some examples that may suggest general principles seem just appropriate, as well as its implementation as design guidelines. Several variables have been considered in the study of the envelope openings: natural ventilation, light and shadow management, connection to the outside and the perception of users in addition to the opening's own characteristics and their relationship with the living space.